The Role of Christian Education in Reducing the Failure of Local Wisdom-based Christian Leadership Ethics - Zalukhu, Amirrudin (Harati: Jurnal Pendidikan Kristen, 2025)
This article explores the role of Christian education in mitigating ethical failures in Christian leadership, using a qualitative literature review approach. Ethical failures in Christian leadership have become a significant concern, as they undermine the integrity and credibility of church leaders, impacting both congregations and society. The paper examines scriptural principles and theological perspectives that shape ethical leadership, emphasizing the importance of character, integrity, and accountability as essential components of Christian leadership. Key passages from the Bible, such as 1 Timothy 3:1-7 and Titus 1:5-9, are analyzed to highlight the ethical expectations for church leaders. Furthermore, the study delves into how Christian education plays a transformative role in shaping the moral and ethical development of leaders, through the integration of theology, ethics, and practical leadership skills. The findings suggest that Christian education provides a foundation for character formation, spiritual growth, and the cultivation of godly leadership practices. By fostering an environment of accountability and ethical training, Christian education can help prevent ethical lapses in leadership and contribute to the restoration of moral integrity in church leadership.